Implementasi Pendidikan Karakter di Sekolah Menengah Pertama Negeri Kabupaten Maros - Sukmawati Sukmawati (Jurnal Ad'ministrare, 2017)
This study aims to determine the form of activities in intrakurikuler and approach to the implementation of education and the inclusion of character values in students in SMP Negeri 5 Mandai Maros District. This research was conducted by using qualitative descriptive analysis and data collection techniques used were documentation and interview. primary data sources are teachers and students, while secondary data are documents related to study materials, including education and cultural ministerial regulations. The results showed that the form of activities and approaches to the implementation of education and the inculcation of character values in students at SMPN.5 Mandai, Maros District, conducted through intrakurikuler activities with integration approach. However, in the implementation of character education through intrakurikuler activities, teachers have not maximized to perform the integration of character value investing, especially in core activities and in closing activities. While the content of teacher learning materials already contain the character values, especially on the 6 subjects that have been analyzed the Plan of Execution of its Learning.